Character Education Values in The Text of The Tumenggung Mask Wayang Against The Slangit Style Jinggananom and Its Use in Literature Learning - Alkhowarijmi, Daniel Fikri; Taiman; Amin, Arip (IJESS International Journal of Education and Social Science, 2024)
This study aims to describe the educational values ??contained in the Slangit style mask puppet performance. From the data obtained, this study describes the dance movements, characters/characterization, stories, and character education values ??reflected in the performance. The objectives of this study are (1) to describe the Slangit style mask puppet art. (2) to describe the character education values ??contained in the performance, and. (3) to describe the character education values ??in the Slangit style mask puppet as a source of implementation in literature learning. The results obtained by the researcher are in the form of a description of the Slangit mask puppet art, the results of a study of the educational values ??contained in the dance movements and the story of Tumenggung vs. Jinggananom, and the use of stories in literature learning.